PENINGKATAN HASIL BELAJAR IPS MELALUI PEMBELAJARAN KOOPERATIF TEKNIK JIGSAW PADA SISWA KELAS VIII SMP NEGERI 2 RA’AS - Alinata, Syaiful Rijal (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2016)
Based on the observations of the students of class VIII SMPN 2 Ra'as a picture that this class is a class that is passive. The indicator is the lack of participation of students in participating subjects. Students tend to be quiet, the courage to ask and answer the question too less. So that the process of learning seem less showed significant activity. Such conditions clearly resulted in student achievement in social studies. Evident from the average value of daily tests, only 13 out of 24 students or 54.17% stated achieve KKM. The purpose of this study was to find out the increase learning outcomes through the use of IPS jigsaw cooperative learning techniques in class VIII SMP Negeri 2 Ra'as the academic year 2015 / 2016. Data collection for student activities conducted by observation, and to the results of study conducted by retrieving data of the results of daily tests. Data was analyzed using qualitative descriptive analysis techniques. Based on the results of data analysis can be concluded: The results of students in the learning process material IPS Events Around Proclamation and process of formation of the Homeland with cooperative learning methods Jigsaw model increased 12.5%, from 79.17% (complete classical) in cycle I became 91.67% (complete classical) in the second cycle.